2015
DOI: 10.1126/science.aaa5267
|View full text |Cite
|
Sign up to set email alerts
|

Spring-loaded unraveling of a single SNARE complex by NSF in one round of ATP turnover

Abstract: During intracellular membrane trafficking, N-ethylmaleimide-sensitive factor (NSF) and alpha-soluble NSF attachment protein (α-SNAP) disassemble the soluble NSF attachment protein receptor (SNARE) complex for recycling of the SNARE proteins. The molecular mechanism by which NSF disassembles the SNARE complex is largely unknown. Using single-molecule fluorescence spectroscopy and magnetic tweezers, we found that NSF disassembled a single SNARE complex in only one round of adenosine triphosphate (ATP) turnover. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 67 publications
8
76
0
Order By: Relevance
“…A hairpin structure inside the central pore has been demonstrated for other AAA ATPases, and there is even evidence that three strands can be present (Burton et al, 2001). This mechanism differs from that of NSF, where the SNARE substrate is not translocated through the central pore, although the D1 ring has canonical pore residues(Zhao et al, 2015), and a single ATPase cycle disassembles the SNARE complex (Ryu et al, 2015). …”
Section: Discussionmentioning
confidence: 97%
“…A hairpin structure inside the central pore has been demonstrated for other AAA ATPases, and there is even evidence that three strands can be present (Burton et al, 2001). This mechanism differs from that of NSF, where the SNARE substrate is not translocated through the central pore, although the D1 ring has canonical pore residues(Zhao et al, 2015), and a single ATPase cycle disassembles the SNARE complex (Ryu et al, 2015). …”
Section: Discussionmentioning
confidence: 97%
“…NSF is a vesicle-fusing ATPase that binds SNARE complexes to separate them during ATP hydrolysis and disassembly of the SNARE complex (87). The PDZ-binding motif takes the form -(D/E)(S/T)X, where X is promiscuous and is a hydrophobic residue.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al found that α-SNAP arrests the trans-SNARE complex in a half-zippered state, thereby preventing fusion in a membrane curvature-dependent manner (Park et al, 2014). Ryu et al observed that α-SNAP destabilizes the C-terminus of the SNARE complex but not enough to form the half-zippered state (Ryu et al, 2015). In contrast, Zick et al found that the yeast α-SNAP homologue, Sec17, strongly promotes trans-SNARE folding and triggers membrane fusion (Zick et al, 2015).…”
Section: Introductionmentioning
confidence: 99%